First day critter jitters - John, Jory (Dial Books for Young Readers, 2020)
"It's almost the first day of school, and the animals are nervous. Sloth worries about getting there on time, snake can't seem to get his backpack fastened onto his body, and bunny is afraid she'll want to hop around instead of sitting still. When they all arrive at their classroom, though, they're in for a surprise: Somebody else is nervous too. It's their teacher, the armadillo! He has rolled in as a ball, and it takes him a while to relax and unfurl. But by the next day, the animals have all figured out how to help one another through their jitters. School isn't so scary after all"--FantasticFiction.com.